THE OPTIMIZATION OF LEADERSHIP MEDIATION, WORK ENVIRONMENT, AND COMMUNICATION FOR EMPLOYEE PERFORMANCE IN DISTRICT SERVICE DIVISION IN PT. STATE ELECTRICITY COMPANY - Fatimah, Nuzulul; Anis Eliyana; Noneng R Sukatmadiredja; Ilham, Ilham; Tatag Herbayu L; Abid Fareed; Heri Cahyo Bagus Setiawan (Dinasti Publisher, 2020)
This study identifies and analyzes optimization by work morale to mediate leadership style, work environment, and communication on the performance of employees of PT. State Electricity Company (PLN PERSERO) Customer Service Unit. This research was conducted using a quantitative, descriptive approach. The population in this study were employees of PT. State Electricity Company (PLN PERSERO) of the Customer Service Unit, amounting to 48. We use path analysis techniques to determine the direct and indirect relationship between leadership style, work environment, and communication on employee performance. As well as how the enthusiasm of work mediates the variables of leadership, work environment, and communication on the performance of employees in the Nuisance Services Division at the PT State Electricity Company, Network Service Unit. The results of this study conclude that (1) leadership style has a positive effect on morale, (2) leadership style directly has a positive effect on work performance, (3) work environment has a positive effect on morale, (4) the work environment directly has a positive effect on work performance. (5) Communication has a positive effect on morale, (6) communication directly has a positive effect on work performance, (7) work performance has a positive effect on morale. (8) Leadership style indirectly positively influences work performance through work morale as an intervening variable, (9) work environment has a positive effect on work performance through work morale as an intervening variable, (10) communication style positively influences work performance through work morale as an intervening variable in service division employees at PT. State Electricity Company (PLN PERSERO) Customer Service Unit.